P.193 Competitive Flow Diversion: Proposed Classification System. (November 2021) - MacLean, MA; Huynh, T; Schmidt, M; Pereira, VM; Weeks, A
Abstract : Background: Competitive flow diversion (CFD) is a novel application of flow diversion stenting (FDS), redirecting flow into a normal artery proximal or distal to the aneurysmal parent artery. A classification system for CFD has not been previously reported. Methods: Report of operative technique and novel classification system for CFD. Results: A patient with subarachnoid haemorrhage and three aneurysms arising from the Pcomm-P1 complex, was treated with endovascular coiling and CFD. The PCOM aneurysm was coiled. Two aneurysms arose from the distal right P1- PCA. After a failed attempt to treat with FDS across the P1-PCA, the P1-aneurysms were successfully treated with CFD distal to the P1-PCA, from Pcomm to P2. Over 12 months, CFD redirected flow via ICA-Pcomm-P2, reducing the size of the P1-PCA, obliterating the P1-aneurysms. Herein, we classify competitive flow diversion into two types. Type I CFD is when the parent artery harbouring the aneurysm is "jailed" proximally. Type II CFD occurs when flow is diverted from the parent artery distal to the aneurysm origin. Conclusions: Herein, we propose a novel classification for CFD. We describe the first case of aneurysm occlusion in the circle of Willis with Type II CFD, and use of CFD for the treatment of multiple adjacent aneurysms.